Hubungan Pemberian Reward Dengan Motivasi Kerja Perawat Pelaksana Di Ruang Rawat Inap Kelas III Rumah Sakit Umum Daerah Raa Soewondo Pati - Fatmawati, Ana Dwi, Supratman, Ph.D (2016)
Introduction: Professional nursing care services and quality are the main targets to be achieved to improve the quality of the Hospital. To realize the competitive health care, the need for management and development of health resources in the face of various challenges. Ranging from distribution, low work ethic, expertise uneven and other management problems. Therefore, the hospital nurse requires professionalism in the work, be it nurses and managers in providing nursing care in accordance with the standards of professional nursing practice. Objective: This study aimed to determine the relationship between reward and motivation nurses working in inpatient hospital grade III RAA Soewondo Pati. Methods: Correlation method used in this study. Research conducted at the Hospital RAA Soewondo Pati in the inpatient unit class III. The population in this study were 101 nurses which consists of seven inpatient class III. The samples in this study using proportional random sampling. So we get the total sample of 54 respondents. The research instrument used questionnaire. Analysis of the data used in this study is univariate and bivariate analysis using Spearman Rank. Results: The data showed that the rate of reward on the nurses in the inpatient unit class III category is being demonstrated with the results of the percentage (72.2%) were 39 respondents. Yield data for the level of work motivation of nurses in the inpatient unit class III Hospital Pati Soewondo RAA also in the medium category with the result percentage (66.7%) With a probability value p value < 0.05 with a correlation coefficient of 0.845, which means there is a great relationship R square strong with 72.8%. Conclusion: There is a significant relationship between reward and motivation nurses working in inpatient hospital grade III RAA Soewondo Pati. Keywords: Reward, Work motivation, Nurse